Next-Generation Sequencing Technologies: Transforming Our Understanding of Human Gene Expression - Omear, Hadeel A. (American Journal of Biomedicine and Pharmacy, 2025)
The new next-generation sequencing technologies have revolutionized human gene expression profiling in search of a deep and precise understanding across divergent conditions and tissues. Hence, RNA sequencing became a very important technology in judging whether it accurately identifies the differential expression of genes between the states of healthy ones and diseases strongly supported by extremely advanced pipelines existing for bioinformatics and stringent validation with concordance with qRT-PCR well above 90%. The DEGs were shown to be highly relevant biologically, regarding the crucial biological processes of immune response and MAPK signaling, using functional analyses by GO and KEGG pathway enrichment Furthermore, classification of health conditions through gene expression utilized a neural network model, whereby it obtained an accuracy of 64.52 % with good sensitivity to detect the diseased samples. This study not only highlights capability of NGS technologies for potential clinical application, but also emphasizes biological discovery at the same time exposing issues ranging from class imbalance in prediction models to poor data quality along with the employment of more evolved methodologies for rectification. All these have shown the transformative nature that NGS can be for precision medicine and transcriptomics.